(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
لقد كان التوجه العالمي بعد نهاية الحرب العالمية الثانية بارزاً في السعي لإنشاء التكتلات الاقتصادية العملاقة وكان أبرزها الاتحاد الأوروبي، ونتيجة للعلاقات القديمة التي ربطت الدول العربية بالدول الأوروبية فقد أثر قيام هذا الاتحاد بعملته الموحدة على مختلف نواحي الاقتصاد في مختلف الأقطار العربية، كما أثر بشكل خاص على القطاع المصرفي العربي في أوروبا من حيث تحرير النشاط المصرفي الأوروبي واعتماد مبادئ لجنة بازل لتنظيم النشاط المصرفي والإشراف عليه، كما أن إطلاق اليورو أثر على حركة التبادل التجاري بين الدول العربية والأوروبية، حيث أصبحت هذه الحركة مرتبطة إلى حد كبير بارتفاع وانخفاض سعر صرف اليورو في حين لم تكن كذلك عندما كان الدولار هو العملة الوحيدة لتسعير المنتجات حتى الداخلة إلى أوروبا وسنحاول في هذا البحث أن نعرض هاتين النقطتين بشيء من التفصيل. The world tendency after the end of the Second World War was distinctive in seeking the establishment of gigantic economical blocs; the most prominent of which was the European Union. Due to the old relationships that connected the Arab Countries with the European Countries, the establishment of this Union with its Unified Currency affected the various economical aspects in the various Arab Countries. Furthermore, it affected in particular on the Arab Banking Sector operating in Europe as regards the release of the European Banking Activity and the reliance on the Principles of Basal Committee for regulating the banking activity and supervising thereon. Also the launching of the Euro affected the commercial exchange movement among the European and Arab Countries, where this movement became connected to a great extent with the rise and fall of Euro Exchange Rate ; while it has not been so when the Dollar was the only currency for pricing the products even those entering Europe. We will try in this Research to handle these two points in some detail.